Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Numbered-Head Together (Nht) Terhadap Peningkatan Aktivitas Belajar Siswa - Arini Alhaq; Uus Manzilatusifa; Bella Anantha Sritumini (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2015)
The learning model Numbered-Head Together (NHT) is one model that can be influenced to improve students' learning activities meaningful learning model Numbered-Head Together (NHT) focus more on the students to groups that are designed to affect the pattern of interaction of students and provide opportunities for students to participate actively in the learning process so as to achieve the learning objectives in accordance with the learned. With the formulation of the problem that arises that is: how much influence is the application of the Numbered-Head Together (NHT) Co-operative Learning Model to the improvement of student learning activities? ". And the purpose of this research is "To know the effect of applying cooperative learning model type Numbered-Head Together (NHT) to Increasing Activity and Social Studies learning. The research method used in this study by using experimental methods, while the nature of research in this study is quantitative. The results showed that: (a) From result of hypothesis test analysis of student activity known that there is influence from applying cooperative model of Numbered-Head Together (NHT) in experiment class,(b) the application of cooperative learning model Numbered-Head Together (NHT) resulted in increasing calculations.